KONTRIBUSI SIKAP ILMIAH DAN SIKAP PEDULI LINGKUNGAN TERHADAP PRESTASI BELAJAR ILMU ALAMIAH DASAR MAHASISWA PRODI PGSD UNIVERSITAS SLAMET RIYADI TAHUN AKADEMIK 2014/2015 - Ratna Widyaningrum, Anggit Grahito Wicaksono & (Widya Wacana: Jurnal Ilmiah, 2016)
The purpose of this study was to determine: (1) whether the scientific attitude has a positivecontribution toward student’s achievement. (2) whether the environmental care attitude has apositive contribution toward student’s achievement. (3) both of the scientific attitude and theenvironmental care attitude have a positive contribution toward student’s achievement. Theprimary data on this research obtained from the questionnaire. The analysis technique using avalidity test, regression analysis, t test, F test, the coefficient of determination test and analysis ofclassical assumptions. The t-test results on the first equation can be concluded that the scientificattitude variables contribute positively and significantly toward student’s achievement. Testresults t-test in the second equation can be concluded that environmental care attitude variablescontribute positively and significantly toward student’s achievement. The t-test results in the thirdequation can be concluded that the scientific attitude and enviromental care attitude contributepostively and significantly toward student’s achievement. The F test results can be concludedboth of scientific attitude and environmental care attitude contributes toward natural sciencelearning achievement on collage students; primary teacher education slamet riyadi surakartauniversity academic year 2014/2015. The result of R2 value is 0.486, it’s mean the totalproportion of variables influence the scientific attitude and a environmental care attitude towardsthe environment variable learning achievement is 48.6%. While the remaining 51.4% (100% -48.6%) influenced by other variables. Classical assumption test results of multiple linearregression can be termed as a good model because the model to meet the assumptions ofnormality and free from classical assumptions.Keywords: Scientific Attitude, Attitude Environmental Care, Learning Achievement